(1166) the econometric approach to studying business cycles: the general model and spectral analysis المنهج الاقتصادي القياسي لدراسة الدورات الاقتصادية: النموذج العام والتحليل الطيفي - el-jarhy, mabid ali mohamed mahmoud (the institute of national planning, 2018)
the econometric approach includes the simultaneous equation model approach, and the use of spectral analysis in studying economic fluctuation. the latter approach is discussed below, and this part takes up the former one.